Translation and cross-cultural adaptation of the mixed methods appraisal tool to the brazilian context / Tradução e adaptação transcultural do instrumento mixed methods appraisal tool ao contexto brasileiro - Rafaella Queiroga Souto; Karina Sotero de Araújo Lima; Pierre Pluye; Quan Nha Hong; Kimberly Barbosa; Gleicy Karine Nascimento de Araújo (Universidade Federal do Estado do Rio de Janeiro, 2021)
Objective: Transculturally translate and adapt the Mixed Methods Appraisal Tool to the Brazilian reality. Methods: The methodology followed the 10 steps determined by the transcultural translation and adaptation process conducted by one of the Working Groups of the Special Interest Group on Quality of Life and the Cultural Translation and Adaptation Group. Results: o The test with the instrument was carried out from the development of two systematic systematic reviews. The translated version obtained a strong / substantial Kappa coefficient (k = 0.67), and was titled "Method of evaluating the quality of researches with mixed methods - Version 2011". The produced version presents structural and semantic components compatible with those of the original version, allowing good understanding and brings clarity in its content. Conclusion: the translated and adapted instrument can be an important tool for scientific production in Brazil, optimizing the production of systematic reviews in the different areas of knowledge.